2011
DOI: 10.1021/ja202755x
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Deposited Organic–Inorganic Hybrid Multilayer Gate Dielectrics. Design, Synthesis, Microstructures, and Electrical Properties with Thin-Film Transistors

Abstract: We report here on the rational synthesis, processing, and dielectric properties of novel layer-by-layer organic/inorganic hybrid multilayer dielectric films enabled by polarizable π-electron phosphonic acid building blocks and ultrathin ZrO(2) layers. These new zirconia-based self-assembled nanodielectric (Zr-SAND) films (5-12 nm thick) are readily fabricated via solution processes under ambient atmosphere. Attractive Zr-SAND properties include amenability to accurate control of film thickness, large-area unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(183 citation statements)
references
References 83 publications
9
172
2
Order By: Relevance
“…They expect that a rational combination of the luminescent property of polyoxometalate clusters with the electric response of reduced graphene oxide films could lead to logic-gate devices with dual optical and electrical output functions. Ha et al 44 demonstrated preparation of self-assembled nanodielectrics with alternate structures of organic and inorganic layers, where polarizable, phosphonic acid-functionalized organic precursors and ultrathin layers of high-k inorganic oxide materials were used ( Figure 10). The ultrathin dielectric materials obtained were adherent, insulating, high-capacitance and thermally stable.…”
Section: Physicochemical Applicationsmentioning
confidence: 99%
“…They expect that a rational combination of the luminescent property of polyoxometalate clusters with the electric response of reduced graphene oxide films could lead to logic-gate devices with dual optical and electrical output functions. Ha et al 44 demonstrated preparation of self-assembled nanodielectrics with alternate structures of organic and inorganic layers, where polarizable, phosphonic acid-functionalized organic precursors and ultrathin layers of high-k inorganic oxide materials were used ( Figure 10). The ultrathin dielectric materials obtained were adherent, insulating, high-capacitance and thermally stable.…”
Section: Physicochemical Applicationsmentioning
confidence: 99%
“…Ever since the pioneering studies in 1993 [124,125], organic-inorganic mono- and multilayer films gained significant attention for their tunable thicknesses, processing ease and insulating properties leading to their integration in organic transistors [6,7,44,126,127]. Especially, recently developed self-assembled nanodielectrics (SANDs) were found to exhibit promising properties for a variety of opto-electronic applications, including thin-film transistors (TFTs) (Figure 6) [7,126128].…”
Section: Flexibility Of Organic-inorganic Nanolayersmentioning
confidence: 99%
“…To this end, many studies on the development and application of new dielectric materials with low leakage current, high dielectric constant, and facile process have been reported [39][40][41][42][43][44][45][46][47][48]. Among them, organic-inorganic hybrid dielectrics might synergistically combine the advantages of both materials, i.e., the excellent mechanical and electrical properties of inorganics and the flexibility and large area solution processibility of organics [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, organic-inorganic hybrid dielectrics might synergistically combine the advantages of both materials, i.e., the excellent mechanical and electrical properties of inorganics and the flexibility and large area solution processibility of organics [41][42][43][44]. One of the representative examples is organosilicate materials, a type of silica containing organic groups.…”
Section: Introductionmentioning
confidence: 99%